"Data" As Vital Illusion. (August 2013) - Koro-Ljungberg, Mirka
I produce data. You produce data. She produces data. We produce data. They produce data. Data is being produced. Data produces us. Data. Data. Data. . . . But only illusions of "data." Copies of "data." ∞